Foreign Bank Entry, Performance of Domestic Banks, and Sequence of Financial Liberalization - Bayraktar, Nihal (World Bank, Washington, D.C., 2013)
The openness or internationalization of financial services is a complex issue because it is closely related to structural reforms in the domestic financial sector with some perceived implications for macroeconomic stability. The authors investigate the impact of foreign bank entry on the performance of domestic banks and how this relationship is affected by the sequence of financial liberalization. Their data set is constructed from the BANKSCOPE database, including 30 industrial and developing countries, and covering the period from 1995 to 2002. The authors apply panel data regressions by pooling all countries together, and by grouping countries according to the sequence of their financial liberalization. One observation based on descriptive analysis is that the degree of openness to foreign bank entry varies a great deal, which is not correlated with average income levels or with GDP growth. Second, the sequence of financial liberalization matters for the performance of the domestic banking sector: After controlling for macroeconomic variables and grouping countries by their sequence of liberalization, foreign bank entry has significantly improved domestic bank competitiveness in countries that liberalized their stock market first. In these countries, both profit and cost indicators are negatively related to the share of foreign banks. Countries that liberalized their capital account first seem to have benefited less from foreign bank entry compared with the other two sets of countries.